P721 Treatment of Ulcerative Colitis with OSE-127 (lusvertikimab), a Strict IL-7Rα Antagonist, Non-Cytotoxic Monoclonal Antibody. (30th January 2023) - Corallo, F; Corallo, Frédérique; Baccelli, Irène; Belarif, Lyssia; Teppaz, Géraldine; Caroline, Mary; Fromond, Claudia; Girault, Isabelle; Pengam, Sabrina; Soma, Emilienne; De Sa, Fanny; Conduzorgues, Jean-Pascal; et al.
Abstract: Background: Key transcripts of the IL-7R pathway were shown to accumulate in inflamed colon tissues of severe IBD patients not responding to conventional or biologics therapies. Furthermore, high expression of both IL7R and IL-7R signaling signature in the colon before treatment is strongly associated with non-responsiveness to anti-TNF therapy. We have designed a humanized monoclonal antibody targeting the IL-7Rα chain, named OSE-127 (lusvertikimab), which displays strict antagonist activity without cytotoxicity nor internalizing properties. In an ex vivo culture system using colon biopsies from UC patients, OSE-127 altered synthesis of interferon γ by Teff . In addition, IL-7R blockade by OSE-127 in humanized mouse models reduced human T cell homing to the gut and colonic inflammation (Belarif L et al, 2019). Methods: A first-in-human, phase I, randomized, double-blind, placebo-controlled, single-center study was carried out to determine the safety, pharmacokinetics and pharmacodynamics of OSE-127 administration. Results: Sixty-three healthy subjects were randomly assigned to OSE-127 or placebo with 45 of them exposed to the active product in 9 groups: 6 single ascending dose groups with intravenous (IV) administration (0.002-10 mg/kg), 1 subcutaneous treatment group (1 mg/kg) and 2 double IV infusion groups (6 or 10 mg/kg). OSE-127 was well tolerated, with no evidence of cytokine-release syndrome and no significant alteration of blood lymphocyte counts or subset populations. OSE-127's pharmacokinetic half-life after a single dose increased from 4.6 days (1mg/kg) to 11.7 days (10 mg/kg) and, after a second dose, from 12.5 days (6 mg/kg) to 16.25 days (10 mg/kg). Receptor occupancy was ≥ 95% at doses ≥ 0.02 mg/kg and this saturation level was maintained up to >100 days after 2 IV infusions at 10 mg/kg. Furthermore, a differential gene expression signature performed in peripheral leukocytes, pre- and post-OSE-127 administration, identified six IL-7 pathway-related genes (BCL2, CISH, PTGER2, DPP4, SOCS2 and FLT3LG). Interestingly, decreased expression of this signature was sustained overtime in accordance with the systemic drug exposure. The differential expression of 4 of these 6 genes (BCL2, CISH, PTGER2, DPP4) has been individually validated by quantitative RT-qPCR, and this novel 4-gene signature appears to follow a dose-dependent expression. Conclusion: Our data provide evidence that IL-7 receptor can be blocked in humans without inducing serious adverse events. The signature identified in the peripheral leukocytes of subjects having received OSE-127 represents a robust and simple means to monitor target engagement in the clinical setting. OSE-127 is currently being evaluated in a Phase 2b study in UC patients (CoTikiS study: NCT04882007).